Penerapan Algoritma Apriori Untuk Menentukan Penjualan Produk Pada Minimarket Studi Kasus Indomaret Ruko Ventura - Nurhadi Surojuddin1; Khoerrudin Khoerrudin (Teknik Informatika, Universitas Pelita Bangsa, 2019)
The Indomaret shop at the Ventura shop is one of the shops that sells various daily necessities. Every day there are sales transactions of various items. However, Indomaret management does not know the pairs of items that consumers often buy simultaneously, so there is often a lack of stock on items that consumers often buy simultaneously. Data mining techniques have been widely used to overcome existing problems, one of which is the application of the Apriori algorithm to obtain information about associations between products from a transaction database. Shop transaction data can be reprocessed using a data mining application so as to produce strong association rules between sales items so that members can recommend the stocking of goods in stores, especially goods purchased simultaneously by consumers and an increase in goods sold in stores. Keywords: Minimarket stores, sales transactions, data mining, Apriori algorithm.Pendahuluan